2017
DOI: 10.18632/oncotarget.23523
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing ofSMOC1in traditional serrated adenoma and colorectal cancer

Abstract: Colorectal sessile serrated adenoma/polyps (SSA/Ps) are well-known precursors of colorectal cancer (CRC) characterized by BRAF mutation and microsatellite instability. By contrast, the molecular characteristics of traditional serrated adenoma (TSAs) are not fully understood. We analyzed genome-wide DNA methylation in TSAs having both protruding and flat components. We identified 11 genes, including SMOC1, methylation of which progressively increased during the development of TSAs. SMOC1 was prevalently methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…Our immunohistochemical analysis revealed that SMOC1 expression is reduced in TSAs, whereas it is abundantly expressed in normal colon and SSA/Ps [15]. This suggests that SMOC1 could be a useful marker for discriminating SSA/Ps from TSAs.…”
Section: Epigenetic Silencing Of Secreted Protein Acidic and Rich In mentioning
confidence: 65%
See 4 more Smart Citations
“…Our immunohistochemical analysis revealed that SMOC1 expression is reduced in TSAs, whereas it is abundantly expressed in normal colon and SSA/Ps [15]. This suggests that SMOC1 could be a useful marker for discriminating SSA/Ps from TSAs.…”
Section: Epigenetic Silencing Of Secreted Protein Acidic and Rich In mentioning
confidence: 65%
“…Analysis using CRC cell lines showed that SMOC1 methylation is associated with gene silencing, and ectopic expression of SMOC1 suppressed CRC cell proliferation and xenograft formation in nude mice, which is indicative of its tumor suppressor function. Collectively, these results suggest that SMOC1 methylation may play a key role in the development of TSAs and adenomas that could progress to CIMP-low CRCs [15].…”
Section: Epigenetic Silencing Of Secreted Protein Acidic and Rich In mentioning
confidence: 77%
See 3 more Smart Citations